A visible light mediated synergistic catalyst for effective inactivation of E. coli and degradation of azo dye Direct Red-22 with mechanism investigation. Issue 79 (9th August 2016) - Naraginti, Saraschandra; Li, Yi; Wu, Yunbo
Abstract : Novel zirconium and silver co-doped TiO2 nanoparticles were fabricated and utilized as effective multifunctional visible light photocatalysts for inactivation of bacteria ( E. coli ) as well as degradation of azo dye (Direct Red-22) for the first time. Abstract : Novel zirconium and silver co-doped TiO2 nanoparticles were fabricated and utilized as effective multifunctional visible light photocatalysts for inactivation of bacteria ( E. coli ) as well as degradation of dye pollutant (Direct Red-22) for the first time. Results revealed co-doping of Ag and Zr in the lattice of TiO2 could remarkably narrow the band gap (2.82 eV) indicated by UV-Vis and photoluminescence studies. The degradation pathway for Direct Red-22 (50 mg L −1 ) proposed using LC-MS, reveals the breaking of the dye into low-toxic metabolites after 5 h. The bactericidal effect against E. coli was found to be high for Zr/Ag–TiO2 (100% inhibition) compared to Ag–TiO2 (74% inhibition) and Zr–TiO2 (48% inhibition), which was further supported by TEM and K + release assay (3.21, 2.34 and 1.62 ppm of K + for Zr/Ag–TiO2, Ag–TiO2 and Zr–TiO2, respectively). DNA analysis indicated no fragmentation during inactivation. Detailed analysis of the reaction mechanism was performed by active species (˙OH and O2 ˙ − ) trapping experiments, NBT transformation and terephthalic acid-photoluminescence probing technique (TA-PL). The activity is found to correlate with the concentration of radicals and is found to be maximum for Zr/Ag–TiO2 . This work is expected to provide new insights into multifunctional nanomaterials for applications in solar photocatalytic degradation of harmful organics and common pathogenic bacteria in wastewater.